Amazing Leonardo da Vinci inventions you can build yourself - Anderson, Maxine (Nomad Press, 2006)
"Introduces readers to the life, world, and incredible mind of Leonardo da Vinci through hands-on building projects that explore his invention ideas." --From publisher's description.